Dietary patterns and depressive symptoms among menopausal women - Oiendrila Baroi; Md Monir Hossain Shimul; Mare- Cha; Salamat Khandker (Clinical Nutrition Open Science)
SUMMARY: Backgrounds and aims: Menopausal women experience physiological and psychological challenges, with depression being a prevalent concern. Dietary intake has been linked to mental health outcomes, yet evidence from low- and middle-income countries, including Bangladesh, remains limited. This study was carried out to find out the association between dietary patterns and depressive symptoms among menopausal women from two distinct socioeconomic groups in Dhaka. Methods: A cross-sectional study of 310 menopausal women in Dhaka was conducted using systematic random sampling from July 2024 to October 2024. Data were collected using a semi-structured questionnaire, the Major Depression Inventory (MDI) scale was used to assess depressive symptoms. Chi-square tests and confidence interval were performed to assess associations between variables. Results: Significant socioeconomic disparities were observed between selected groups (housing society and slum residents). Housing society residents had greater access to nutrient-rich foods, consuming fruits daily (94.83% vs. 0%, P < 0.001) and milk weekly (46.45% vs. 1.93%, P < 0.001). In contrast, slum residents had a higher intake of leafy vegetables (77.41% vs. 54.19%, P = 0.011) and Pangus fish (69.03% vs. 27.74%, P < 0.001). Meal skipping was more frequent among slum dwellers (49.02% vs. 20.64%, P < 0.001). Severe depression was significantly higher in slum residents (47.74% vs. 36.12%, P = 0.038), and moderate depression followed a similar trend (39.35% vs. 29.03%, P = 0.025). Conclusions: Socioeconomic status significantly influences dietary intake and depressive symptoms among menopausal women in Bangladesh. Nutritional education and mental health services may be initiated for slum dwellers.